LARVAE OF THE INDIAN MACKEREL, RASTRELLIGER KANAGURTA (CUVIER) FROM THE WEST COAST OF INDIA - Silas, E G (Indian Journal of Fisheries, 2011)
Larvae of the Indian mackerel, Rastrelliger kanagurta (Cuvier) have been identified by the author from the plankton of the south west coast of India and the Laccadive Sea collected during the cruises of R. V. VARUNA. Prolarval and postiarval sta-ges from the size 1.73 mm to 8.6 mm (T.L.) are described from the graded series present in the collections to highlight the salient features during the larval develc^ment. This account also represents the first descriptions with illustrations of the mackerel larvae from the west coast of India. The distribution of the larvae, their occurrence in day and night vertical tovra made with tlae Indian Ocean Standard Net, the relative abundance of larvae in the continental shelf and oceanic waters, their abundance latitude-wise, the size-wise frequency of occurrence of larvae and the Temperature-Salinity, Temperature- Dissolved Oxygen, Saliruty-Dissolved Oxygen relationship to the occurrence of the larva; from 38 out of 92 stations in the month of May 1964 are also discussed.